2017
DOI: 10.1021/acs.joc.7b00703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Immunological Studies of the Lipomannan Backbone Glycans Found on the Surface of Mycobacterium tuberculosis

Abstract: Investigations into novel bacterial drug targets and vaccines are necessary to overcome tuberculosis. Lipomannan (LM), found on the surface of Mycobacterium tuberculosis (Mtb), is actively involved in the pathogenesis and survival of Mtb. Here, we report for the first time a rapid synthesis and biological activities of an LM glycan backbone, α(1-6)mannans. The rapid synthesis is achieved via a regio- and stereoselective ring opening polymerization to generate multiple glycosidic bonds in one simple chemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In a different study, DC-SIGN was also found to interact with the α(1-6)-mannan backbone of lipomannan, another important glycolipid of the M. tuberculosis cell wall (Figure 1, right part). Comparison of DC-SIGN binding to array-printed mannans containing 7, 13, and 19 α(1-6)-linked Man units revealed a clear preference for the longer chains (Leelayuwapan et al, 2017), again indicating that this receptor is able to bind internal Man residues. Moreover, binding of DC-SIGN to other microbial glycans was recently observed using a microarray containing 120 synthetic bacterial structures out of over 300 structures (Geissner et al, 2019).…”
Section: Bacterial Glycan Arrays For Identification Of Ligands For Lementioning
confidence: 93%
“…In a different study, DC-SIGN was also found to interact with the α(1-6)-mannan backbone of lipomannan, another important glycolipid of the M. tuberculosis cell wall (Figure 1, right part). Comparison of DC-SIGN binding to array-printed mannans containing 7, 13, and 19 α(1-6)-linked Man units revealed a clear preference for the longer chains (Leelayuwapan et al, 2017), again indicating that this receptor is able to bind internal Man residues. Moreover, binding of DC-SIGN to other microbial glycans was recently observed using a microarray containing 120 synthetic bacterial structures out of over 300 structures (Geissner et al, 2019).…”
Section: Bacterial Glycan Arrays For Identification Of Ligands For Lementioning
confidence: 93%
“…An approach using a (cationic) ROP method using tricyclic orthoester Man BBs considerably reduced the time needed for the stereoselective synthesis of linear α(1–6)-mannans (ranging from 5mer to 20mer) [ 275 ]. The biggest advantage of this approach is the easy scalability, up to a gram scale.…”
Section: Reviewmentioning
confidence: 99%
“…Attempts to use conjugates of synthetic mannans (Leelayuwapan et al. 2017 ), phosphatidylinositol mannosides (Boonyarattanakalin et al. 2008 ) or rhamnans (Vignal et al.…”
Section: Approaches For Production Of Glycoconjugate Vaccinesmentioning
confidence: 99%